Efferocytosis: An Emerging Therapeutic Strategy for Type 2 Diabetes Mellitus and Diabetes Complications - Liu X; Liu H; Deng Y (Dove Medical Press, 2023)
Xun Liu,1 Hua Liu,2 Yihui Deng1 1Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People's Republic of China; 2Southern Theater General Hospital of the Chinese People's Liberation Army, Guangzhou, Guangdong, 510010, People's Republic of ChinaCorrespondence: Yihui Deng, Email dengyihui@hnucm.edu.cnAbstract: Increasing evidence indicates that chronic, low-grade inflammation is a significant contributor to the fundamental pathogenesis of type 2 diabetes mellitus (T2DM). Efferocytosis, an effective way to eliminate apoptotic cells (ACs), plays a critical role in inflammation resolution. Massive accumulation of ACs and the proliferation of persistent inflammation caused by defective efferocytosis have been proven to be closely associated with pancreatic islet β cell destruction, adipose tissue inflammation, skeletal muscle dysfunction, and liver metabolism abnormalities, which together are considered the most fundamental pathological mechanism underlying T2DM. Therefore, here we outline the association between the molecular mechanisms of efferocytosis in glucose homeostasis, T2DM, and its complications, and we analyzed the present constraints and potential future prospects for therapeutic targets in T2DM and its complications.Keywords: type 2 diabetes mellitus, diabetes complications, efferocytosis, inflammation, apoptosis